Rise of intraocular pressure in a caffeine test versus the water drinking test in patients with glaucoma. (4th December 2013) - Tran, Tuan; Niyadurupola, Nuwan; O'Connor, Jeremy; Ang, Ghee Soon; Crowston, Jonathan; Nguyen, Dan
Abstract Background There is increasing emphasis on the importance of intraocular pressure peaks and fluctuations as risk factors for glaucoma progression. It is well recognized that the water drinking test raises intraocular pressure and there is reasonable evidence that caffeine can also raise intraocular pressure. The aim of this study is to directly compare the effect of a caffeine test to that of the water drinking test on intraocular pressure, in patients with glaucoma. Design Prospective, observer‐masked, cross‐over study. Participants Fourteen eyes of 14 patients with primary open‐angle glaucoma. Methods Patients were initially randomized to either caffeine test or water drinking test. Intraocular pressure was measured in both eyes with a Goldmann applanation tonometer at baseline and every 15 min for 1 h, by a masked examiner. This was repeated the following week at the same time of day for the other test (the cross‐over). Peak intraocular pressure and maximum fluctuation from baseline were compared between groups using paired t‐tests. Main Outcome Measures Peak and fluctuation of intraocular pressure, time of maximum frequency of peak intraocular pressure. Results The maximum intraocular pressure from the water drinking test (19.7 ± 4.1) was greater than the caffeine test (16.7 ± 4.1) and showed greater fluctuation in intraocular pressure (4.3 ± 2.7 mmHg [27.7%]; P < 0.0001) compared with the caffeine test (1.8 ± 1.9 mmHg [11.7%]); P = 0.004). Conclusion The rise in intraocular pressure was greater with water drinking test than the caffeine test. Caffeine does not appear to provide an alternative for patients unable to tolerate the water drinking test.